Error analysis in algebraic operations: Identifying and addressing misconceptions in algebraic learning - Susanti, Dwi; Yulianti, Eka; Noviantari, Ika (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
grade students at SMP Islam Terpadu Ulul Albab Tarakan. The research focuses on identifying the nature of these misconceptions and exploring strategies for improving algebraic learning. Method: A qualitative case study approach was employed, involving six students who demonstrated consistent misconceptions in solving algebraic problems. Data were collected through document analysis of students’ algebraic problem-solving assignments and semi-structured interviews with the students and their mathematics teacher. This triangulation of methods ensured comprehensive data and insights into the students’ misconceptions. Findings: The analysis revealed four primary types of misconceptions: (1) misunderstanding the meaning of algebraic problems, where students mistakenly applied arithmetic strategies; (2) confusion regarding algebraic forms, especially with exponents and coefficients; (3) errors in algebraic operations, such as incorrectly combining unlike terms; and (4) misconceptions in handling operations involving negative and positive numbers, leading to incorrect subtraction. Significance: The study highlights the critical impact of misconceptions on students’ understanding of algebra. It suggests that misconceptions, if left unaddressed, can impede students’ progress in learning advanced mathematics. The findings recommend the use of teaching strategies like Problem-Based Learning (PBL) to foster conceptual clarity and enhance students’ problem-solving abilities. This research provides valuable insights into addressing algebraic misconceptions and improving algebraic education.